Recent advancements in polymer science for retinal diseases: New frontiers in drug delivery systems - Weiliang Wang; Nancy Wang; Xinxin Zhao; Xinyi Su; Zengping Liu (APL Bioengineering)
Retinal diseases, such as age-related macular degeneration and diabetic macular edema, are significant contributors to vision loss. While injection of anti-vascular endothelial growth factors is the current gold standard treatment, their invasive nature reduces patient compliance and treatment outcomes and increases the risk of complications. In this review, we explore the recent advancements in drug delivery systems designed to overcome ocular barriers to effectively deliver drugs to the retina. We examine advancements in intravitreal injections, such as novel formulations, therapeutic molecules, and sustained-release implants. Moreover, we discuss innovations in noninvasive strategies, such as topical delivery systems incorporating cell-penetrating peptides, solid lipid nanoparticles, dendrimers, and nano-micelles. These technologies aim to enhance drug penetration, stability, and bioavailability. Although preclinical and clinical trials have yielded promising results, challenges remain in ensuring long-term safety and efficacy. This review highlights future research directions to optimize these approaches and develop more effective, patient-friendly therapies for retinal diseases.